2013
DOI: 10.1262/jrd.2012-186
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Expressions of Antioxidant Enzymes by Luteinizing Hormone in the Bovine Corpus Luteum

Abstract: Luteoprotective mechanisms of luteinizing hormone (LH) involved in the maintenance of bovine corpus luteum (CL) function have not been completely clarified. Since antioxidant enzymes are well documented as antiapoptotic factors in the CL of many mammals, we hypothesized that the luteoprotective action of LH is mediated by stimulating the local production and action of antioxidant enzymes. To test the above hypothesis, in the present study, we examined the mechanisms involved in the luteoprotective actions of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
15
1
1
Order By: Relevance
“…This suggests the important role that ROS plays during the process of LH‐induced progesterone release. However, a study reported that LH also stimulates the intraluteal expressions of Copper/Zinc‐dependent SOD (Cu/Zn‐SOD), manganese‐dependent SOD (Mn‐SOD), and catalase to maintain the luteal cell viability and ROS balance . This study indicates that LH not only induces ROS production but also regulates it by stimulating the anti‐oxidant enzymes’ expression, thus maintaining the redox state.…”
Section: Physiological Relevance Of Reactive Oxygen Species In Oocytementioning
confidence: 78%
See 2 more Smart Citations
“…This suggests the important role that ROS plays during the process of LH‐induced progesterone release. However, a study reported that LH also stimulates the intraluteal expressions of Copper/Zinc‐dependent SOD (Cu/Zn‐SOD), manganese‐dependent SOD (Mn‐SOD), and catalase to maintain the luteal cell viability and ROS balance . This study indicates that LH not only induces ROS production but also regulates it by stimulating the anti‐oxidant enzymes’ expression, thus maintaining the redox state.…”
Section: Physiological Relevance Of Reactive Oxygen Species In Oocytementioning
confidence: 78%
“…In follicles, apart from mitochondrial respiration and oxidative phosphorylation, some other mechanisms also contribute to ROS release. Luteinizing hormone (LH) signals the corpus luteum to produce and secrete progesterone . The process is highly complex and regulated at several stages enlisted below.…”
Section: Physiological Relevance Of Reactive Oxygen Species In Oocytementioning
confidence: 99%
See 1 more Smart Citation
“…LH regulates a variety of ovarian functions, although its main effect may be to stimulate P 4 secretion by the corpus luteum. In fact, LH strongly stimulates P 4 production by cultured bovine luteal cells (Juengel & Niswender 1999) and plays some luteoprotective roles by increasing luteal cell viability (Kawaguchi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Manganese deficiency in cattle produces a delay in the first estrous (Bentley and Phillips, 1951;Rojas et al, 1965), and in small ruminants not only impairs estrous cycle, but also reduces birth weight (Underwood and Suttle, 1999). LH enhances the viability of lutheal cells by stimulating the intralutheal expression of Mn-SOD, Cu-Zn-SOD and catalase, and by stimulating SOD activity to maintain lutheal function in cows (Kawaguchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%